American silence - Papanikolas, Zeese (Book collections on Project MUSE., 2007)
In American Silence, a complement to his previous study Trickster in the Land of Dreams, Zeese Papanikolas investigates a number of significant American cultural artifacts and the lives of their makers. For Papanikolas, both the private failures and public successes of Clarence King, Henry Adams, Gertrude Stein, Ernest Hemingway, Raymond Chandler, and Hank Williams resonate with silences.